Physicochemical Characteristics and Spoilage Bacteria of Modified Atmosphere Packaged Braised Chicken during Refrigeration - ZHANG Li, MA Yunhao, WANG Ying, XU Baocai (Shipin Kexue, 2023)
In order to explore dynamic changes in the physicochemical characteristics and microbial diversity of modified atmosphere packaged braised chicken during refrigeration, high-throughput sequencing technology and traditional isolation and identification methods were combined to study the physical and microbial changes of modified atmosphere packaged (25% CO2/75% N2) braised chicken during storage at 4 ℃ for 10 days. The results showed that total volatile basic nitrogen (TVB-N) content and total bacterial count increased significantly during storage (P 0.05). These changes were related to the gas composition in modified atmosphere packaging. The microbial species richness of braised chicken was the highest at the early stage of storage, and then decreased gradually. At the initial stage of storage, the relative abundance of Enterobacteriaceae, Acinetobacter and Aeromonas were high. At the middle and late stages of storage, the relative abundance of Weissella and Enterobacter were high. The relative abundance of Weissella, Enterobacter, Lactococcus and Leuconostoc increased gradually during the whole storage period and their growth was dominant. Six species of spoilage organisms were isolated and identified, namely, Lactobacillus curvatus, Bacillus cereus, Bacillus safensis, Serratia liquefaciens, Hafnia sp. and Enterobacter sp., which could be the major causes of the rot of braised chicken under modified atmosphere packaging conditions.